Cascade effects on the irradiation stability of amorphous SiOC. (1st February 2016) - Su, Qing; Cui, Bai; Kirk, Marquis A.; Nastasi, Michael
Abstract: We studied the heavy ion radiation tolerance of amorphous silicon oxycarbide (SiOC) alloys by in situ Kr ion irradiation within a transmission electron microscopy. The amorphous SiOC thin films were grown via co-sputtering from SiO2 and SiC targets on a surface-oxidized Si (100) substrate. These films were irradiated by 1 MeV Kr ions at both room temperature and 300 °C with damage levels up to 5 displacements per atom (dpa). TEM characterization shows no sign of crystallization, void formation or segregation in all irradiated samples. Our findings suggest that SiOC alloys are a class of promising radiation tolerant materials.